The Development of Nonthermal Plasma and Tirapazamine as a Novel Combination Therapy to Treat Melanoma In Situ - Matthew Yehl; Dominik Kucharski; Michelle Eubank; Brandon Gulledge; Gamal Rayan; Md Gias Uddin; Genevieve Remmers; Eugene S. Kandel; Douglas P. DuFaux; Timothy C. Hutcherson; Sandra Sexton; Shoshanna N. Zucker (Cells, 2023)
Although melanoma accounts for only 5.3% of skin cancer, it results in >75% of skin-cancer-related deaths. To avoid disfiguring surgeries on the head and neck associated with surgical excision, there is a clear unmet need for other strategies to selectively remove cutaneous melanoma lesions. Mohs surgery is the current treatment for cutaneous melanoma lesions and squamous and basal cell carcinoma. While Mohs surgery is an effective way to remove melanomas in situ, normal tissue is also excised to achieve histologically negative margins. This paper describes a novel combination therapy of nonthermal plasma (NTP) which emits a multitude of reactive oxygen species (ROS) and the injection of a pharmaceutical agent. We have shown that the effects of NTP are augmented by the DNA-damaging prodrug, tirapazamine (TPZ), which becomes a free radical only in conditions of hypoxemia, which is often enhanced in the tumor microenvironment. In this study, we demonstrate the efficacy of the combination therapy through experiments with B16-F10 and 1205 Lu metastatic melanoma cells both in vitro and in vivo. We also show the safety parameters of the therapy with no significant effects of the therapy when applied to porcine skin. We show the need for the intratumor delivery of TPZ in combination with the surface treatment of NTP and present a model of a medical device to deliver this combination therapy. The importance of functional gap junctions is indicated as a mechanism to promote the therapeutic effect. Collectively, the data support a novel therapeutic combination to treat melanoma and the development of a medical device to deliver the treatment in situ.